Umberto Eco and Emotions in The Time of Internet - Renata Martini Kristo (Association of Social and Educational Innovation, 2017)
"Social networks gives right of speech to legions of idiots". These are the words from Umberto Eco directing an attack on Internet during the ceremony in the University of Torino to award him Honoris Causa for Communication and media culture. After these statements "the network people" felt offended and they launched a harsh attack against the writer. Therefore I decided to get deeply focused on such argument and made researches to create an idea about the writer‟s reflection and tried to formulate a potential personal consideration. The purpose for doing this is not to protect Eco: he is part of those people of reputation in culture who with their work have changed the way we study language and communication, let alone his extraordinary talent as a novelist. I conducted this analysis to better understand his opinion on Internet, social networks and technology. In this reflection I have indicated that his harsh words did not come out of nothing, in contrary, he made similar statements in other cases. The theory developed by him was complete, consolidated and logically argued. Behind this attack lies a reflection on such an important topic for our society: Internet information filtering, necessity of education on internet, things which need to get started since the early school education. At the end of the article I have provided a short information about a platform, an online multimedia compiled by him named Encyclomedia, an encyclopedia based on a new concept which is dedicated to the history of humankind by establishing links between what is searched in internet with relation to literature, science, art, music, economy, society, religion. This project demonstrates the fact that this man regardless of being part of cultural environment of "Novecento" tried to utilize the new technology to the benefit of knowledge and its dissemination.